Regional problems of organic grain production - Voronianska, Olena; Воронянская, Елена Владиленовна; Воронянська, Олена Владиленівна (My University, 2009)
The increasing of agricultural production is impossible without increasing of land use efficiency. For the production of organic food it is necessary to use modem technologies, which are based on the care of soils fertility increasing and its protection from toxic and poisonous substances. However to exclude the toxics and mineral fertilizers — does not mean that you pass to organic production.
Keywords: agricultural production; organic food; food safety of a foodstuff; food value; the product price; potential product deficiency; taste and product marketable state